Studying the role of educational curricula in qualifying students to enter the labor market and prepare for careers (Form for students of the applied college at Tishreen University) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The aim of the research is to identify the role of the curricula used in qualifying students to enter the labor market, and career readiness from the point of view of graduate students from the Applied College at Tishreen University, where the descriptive analytical method was adopted as a research approach, and the questionnaire was also used to collect data and information, where 152 questionnaires were distributed. Students must retrieve it completely, and then analyze it using the spss program.The results of the research showed that the role of the curricula used in developingStudent's skills in accordance with the requirements of the labor market was to a moderate degree, due to the absence of coordination between the educational  institutions responsible for developing curricula and institutions and companies in the public and private sectors to know the skills that these companies need in order toWork on their development among students. And focus on them and the suitability ofThe theoretical subjects studied by students with the requirements of the labor market,And the extent to which the curricula include aspects related to the future of the graduate were also moderate. The research also showed the presence of statisticallySignificant differences at the 5% significance level for the role of the curriculum inDeveloping students, skills in a manner consistent with labor market requirements attributed to the gender variable in favor of male respondents.